Evaluation of Liver Function Tests (LFT) and C-reactive protein in COVID-19 (SARS Cov-2) positive patients diagnosed by Real-time PCR - Fatima Khurshid, Madiha Mumtaz, Sajjad Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background/Aim: Unpredicted social and economic consequences have resulted from the SARS-CoV-2 pandemic worldwide. Limited information is currently available addressing the COVID-19 infection impact on the RT-PCR Cycle threshold value trend, infection risk factors, impact on liver enzymes, etc. Methods: From November 2020 to March 2021, a cross-sectional study was carried out in the Chemical Pathology also Molecular Biology divisions of the Pathology Department of Shalamar Hospital, Lahore. Results: Males had a higher risk of contracting SARS-CoV-2 infection than females about 51%. 36.5 percent of total infected people fell within the 20–40 age range. Significant factors that affect the severity of COVID-19 include age and underlying comorbidities. The majority of the patients (78.3%) reported fever, 50.4% had a cough, and 50.1% had myalgias. Low Ct value of RT-PCR may be asignificant predictor of illness severity and risk of mortality, with p values of 0.001 and 0.003, correspondingly. Disease severity was substantially associated with CRP, AST, ALT, and bilirubin indirect. It was observed that the Deritis ratio and CRP were highly associated with the risk of mortality. These markers can therefore be used to evaluate a patient's status as it progresses toward a severe disease, liver damage from treatment, and death risk. Conclusions: For doctors making patient management decisions, real-time PCR data and Ct values for SARS-CoV-2 may be useful. Age and comorbidities, among other risk variables, have been recognized as being associated with the likelihood of having a fatal illness. ALT, AST, Deritis ratio, and CRP are biochemical laboratory indicators that can be considered prognostic biomarkers for the development of severe disease and risk of mortality. Keywords: SARS-CoV-2, COVID-19, Liver, Cough, Pandemic